A pair of transporters controls mitochondrial Zn2+ levels to maintain mitochondrial homeostasis. Issue 3 (23rd October 2021) - Ma, Tengfei; Zhao, Liyuan; Zhang, Jie; Tang, Ruofeng; Wang, Xin; Liu, Nan; Zhang, Qian; Wang, Fengyang; Li, Meijiao; Shan, Qian; Yang, Yang; Yin, Qiuyuan; et al.
ABSTRACT: Zn 2+ is required for the activity of many mitochondrial proteins, which regulate mitochondrial dynamics, apoptosis and mitophagy. However, it is not understood how the proper mitochondrial Zn 2+ level is achieved to maintain mitochondrial homeostasis. Using Caenorhabditis elegans, we reveal here that a pair of mitochondrion-localized transporters controls the mitochondrial level of Zn 2+ . We demonstrate that SLC-30A9/ZnT9 is a mitochondrial Zn 2+ exporter. Loss of SLC-30A9 leads to mitochondrial Zn 2+ accumulation, which damages mitochondria, impairs animal development and shortens the life span. We further identify SLC-25A25/SCaMC-2 as an important regulator of mitochondrial Zn 2+ import. Loss of SLC-25A25 suppresses the abnormal mitochondrial Zn 2+ accumulation and defective mitochondrial structure and functions caused by loss of SLC-30A9. Moreover, we reveal that the endoplasmic reticulum contains the Zn 2+ pool from which mitochondrial Zn 2+ is imported. These findings establish the molecular basis for controlling the correct mitochondrial Zn 2+ levels for normal mitochondrial structure and functions.